Apresentação - Osti, Andreia; Bacocina, Eliane Aparecida; Gracioli, Filipe Rafael; Pezzato, João Pedro; Chaluh, Laura Noemi; Rodrigues Martins de Camargo, Maria Rosa (Educação: Teoria e Prática, 2021)
Apresentação do Dossiê Paulo Freire faz 100 anos: . . .